2018
DOI: 10.1038/s41564-018-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

A protective human monoclonal antibody targeting the West Nile virus E protein preferentially recognizes mature virions

Abstract: West Nile virus (WNV), a member of the Flavivirus genus, is a leading cause of viral encephalitis in the United States1. The development of neutralizing antibodies against the flavivirus envelope (E) protein is critical for immunity and vaccine protection2. Previously identified candidate therapeutic mouse and human neutralizing monoclonal antibodies (mAbs) target epitopes within the E domain III lateral ridge and the domain I-II hinge region, respectively3. To explore the neutralizing antibody repertoire elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…In addition to potent neutralization of DENV1-4 reporter viruses, which are based on lab-adapted strains isolated between 1964–1982, J9 and J8 also neutralized DENV1-4 strains isolated more recently (between 2004–2007) with IC 50 values < 50 ng/ml (Figure 2—figure supplement 2). Additionally, in contrast to C4 and the cross-reactive DII fusion loop-specific mouse antibody E60 (Goo et al, 2017; Nelson et al, 2008; Oliphant et al, 2006), but similar to EDE bNAbs (Dejnirattisai et al, 2015), J9 and J8 potently neutralized DENV regardless of virion maturation state (Figure 2—figure supplement 3), which can indirectly modulate epitope exposure (Cherrier et al, 2009; Goo et al, 2019; Nelson et al, 2008) and has been shown to be distinct among circulating versus lab-adapted strains (Raut et al, 2019). We also tested the ability of antibodies to mediate neutralization after virus attachment to cells, which is characteristic of many potently neutralizing antibodies against flaviviruses (Goo et al, 2019; Nybakken et al, 2005; Sukupolvi-Petty et al, 2010; Vogt et al, 2009; Xu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to potent neutralization of DENV1-4 reporter viruses, which are based on lab-adapted strains isolated between 1964–1982, J9 and J8 also neutralized DENV1-4 strains isolated more recently (between 2004–2007) with IC 50 values < 50 ng/ml (Figure 2—figure supplement 2). Additionally, in contrast to C4 and the cross-reactive DII fusion loop-specific mouse antibody E60 (Goo et al, 2017; Nelson et al, 2008; Oliphant et al, 2006), but similar to EDE bNAbs (Dejnirattisai et al, 2015), J9 and J8 potently neutralized DENV regardless of virion maturation state (Figure 2—figure supplement 3), which can indirectly modulate epitope exposure (Cherrier et al, 2009; Goo et al, 2019; Nelson et al, 2008) and has been shown to be distinct among circulating versus lab-adapted strains (Raut et al, 2019). We also tested the ability of antibodies to mediate neutralization after virus attachment to cells, which is characteristic of many potently neutralizing antibodies against flaviviruses (Goo et al, 2019; Nybakken et al, 2005; Sukupolvi-Petty et al, 2010; Vogt et al, 2009; Xu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The multifunctional glycosylated E protein is a prototypical class II fusion protein that is an integral part of the virion, participates in viral virulence and virion morphogenesis, and stimulates the production of NAbs [ 26 , 27 ]. One study showed that the specific motif VNDT (containing an N-linked glycosylation) in ZIKV is involved in mouse neuroinvasion [ 28 ].…”
Section: Flavivirus Envelope Protein Structure and Its Functionsmentioning
confidence: 99%
“…Antibodies are critical for the control of flavivirus infection, and this protection has been correlated with neutralizing activity in vitro (26,58,59). The flavivirus E protein is the dominant antigen inducing immunologic responses in infected hosts and eliciting virus-neutralizing antibodies (42,60,61).…”
Section: Discussionmentioning
confidence: 99%